Chemical LTP induces confinement of BDNF mRNA under dendritic spines and BDNF protein accumulation inside the spines - Bimbi, Giorgia; Tongiorgi, Enrico (Frontiers in Molecular Neuroscience, 2024)
The neurotrophin brain-derived neurotrophic factor (BDNF) plays a key role in neuronal development and synaptic plasticity. The discovery that BDNF mRNA can be transported in neuronal dendrites in an activity-dependent manner has suggested that its local translation may support synapse maturation and plasticity. However, a clear demonstration that BDNF mRNA is locally transported and translated at activated synapses in response to long-term potentiation (LTP) is still lacking. Here, we study the dynamics of BDNF mRNA dendritic trafficking following the induction of chemical LTP (cLTP). Dendritic transport of BDNF transcripts was analyzed using the MS2 system for mRNA visualization, and chimeric BDNF-GFP constructs were used to monitor protein synthesis in living neurons. We found that within 15 min from cLTP induction, most BDNF mRNA granules become stationary and transiently accumulate in the dendritic shaft at the base of the dendritic spines, while at 30 min they accumulate inside the spine, similar to the control CamkIIα mRNA which also increased inside the spines at 60 min post-cLTP. At 60 min but not at 15 min from cLTP induction, we observed an increase in BDNF protein levels within the spines. Taken together, these findings suggest that BDNF mRNA trafficking is arrested in the early phase of cLTP, providing a local source of mRNA for BDNF translation at the base of the spine followed by translocation of both the BDNF mRNA and protein within the spine head in the late phase of LTP.